Taxation policy in low-income countries - Christopher Heady (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper discusses the design of tax systems in developing countries, with particular emphasis on low-income countries. It outlines the directions of reform that many lowincome countries have followed, often on the advice of the IMF or the World Bank, and considers whether they are justified in terms of theory and the practical constraints in low-income countries. Discussion of tax theory shows that there are sound reasons for much of the tax reform advice that is given, but it provides rather little support for the policy of full tax neutrality that is frequently recommended for developing countries. However, there are also serious political economy arguments against tax nonuniformity. The paper therefore concludes that the design of tax policy must also consider the strength of institutions and the rule of law. – taxation ; fiscal policy
Keywords: O23; H20; 330; Steuersystem; Steuerpolitik; Entwicklungsländer; Low-Income Countries